(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This article analyzes the effectiveness of introducing innovative technologies in the construction materials industry, the essence of the quality management system, and its integration into the production process. The study highlights the practical results of implementing “green” technologies, ISO 9001:2015 quality management standards, and innovative management approaches in enterprises producing building materials in Uzbekistan.